الإطار المفاهيمي لنظام المحاسبة العمومية في الجزائر - بلول, محمد الصالح; عبود, ميلود (جامعة الوادي University of Eloued, 2019)
تهدف هذه الدراسة إلى التعريف بنظام المحاسبة العمومية المطبق في الجزائر من خلال تبيان مفهومها و خصائصها ونطاق تطبيقها والتمييز والتفريق بين مفاهيم المحاسبة العمومية مع المحاسبة المالية من أجل التحكم الجيد في قواعد المحاسبة العمومية بالجزائر في إطار المبادئ الخاصة بها، والتعرف كذلك على الأعوان المكلفون بالتنفيذ وتحديد الأدوار والمهام الخاصة بهم وكذا صلاحياتهم و مسؤولياتهم كل حسب ما هو محدد له في التشريع الجزائري كل هذا من أجل ضمان تسيير أمثل وحماية أفضل للمال العام. This study aims to introduce the public accounting system applied in Algeria by showing its concept, characteristics and scope of application, distinguishing between the concepts of public accounting with financial accounting for the good control of public accounting rules in Algeria within the framework of its own principles, as well as to identify the agents responsible for implementation and identify Their roles and functions, as well as their powers and responsibilities, as defined in Algerian legislation, are all designed to ensure optimal management and protection of public funds.
The Conceptual Framework of the Public Accounting System in Algeria
مقال
Keywords: المحاسبة العمومية ; الأعوان المكلفون بالتنفيذ ; التشريع الجزائري